The family role model in self-care at schizophrenic patients - Mundakir, Nina Agustina, Ah. Yusuf*, Agung Eko Hartanto, (Opción, 2019)
This study aims to analyze the Family Role Model in improving Self Care in schizophrenic patients using the Theory of Planned Behavior Approach. This study used a cross-sectional design, a sample of 126 families in Ponorogo, Indonesia. Results: Significantly behavioral influences on family roles (t = 3.304> 1.96); intent have an effect on family role (t = 2.885> 1.96). In conclusion, families with schizophrenic patients felt still experience obstacles in relation to mental health services.